Effect of the number of physiologically mature maintenance leaves and the frequency of foliar fertilizer application on the growth of Empoasca, weeds, and the yield of clone GMB 7 tea crop (Camellia sinensis (L.) O. Kuntze) - Odih Sucherman (Research Institute for Tea and Cinchona, 2014)
The objective of this research was to study the interaction effect between the number of physiologically mature maintenance leaves on tipping and the frequency of application foliar fertilizer application on the development of the main pest Empoasca, weeds and the yield of GMB 7 tea clone. The experiment was conducted at Gambung Estate, block A4, Research Institute Tea and Cinchona, Mekarsari Village, Pasirjambu Subdistrict, Bandung Regency, with altitude about 1.300 m above sea level. The average rainfall was 3.035 mm/year and the type of rainfall is B according to Schmidt and Fergusson (1951). The soil type is Andisol with pH 5,9. The experiment was done from December 2011 until July 2012. The experiment has factorial Randomized Block Design (RBD) with three replications. The first factor is physiologically mature maintenance leaves on tipping (A) with 3 treatments: a0 = 3 leaves, a1 = 5 leaves and a2 = 7 leaves. The second factor is the application of follar fertilizer (B) with three treatments: b0 = without application, b1 = one application and b2 = two applications. The result showed that no interaction between the number of physiologically mature maintenance leaves and the frequency of foliar fertilizer application on the attack intensity of Empoasca. The interaction between five physiologically mature maintenance leaves and one application of folliar fertilizer treatment were effective to control pest and weeds. The interaction happened between the number of physiologically mature maintenance leaves on tipping and the frequency application of foliar fertilizer on yield at 10 and 12 weeks after determined the physiologically mature maintenance leaves. The average of LAI on five physiologically mature maintenance leaves and one application of folliar fertilizer treatment were 3,0087 with regression Ŷ-a1b1 = -0,1923 + 0,0237 X; R^2 = 0,8979 were effective to control Empoasca, weeds and to increase the yield.